What could go wrong with cooking? Exploring vulnerability at the water, energy and food Nexus in Kampala through a social practices lens. (July 2020) - Mguni, Patience; van Vliet, Bas; Spaargaren, Gert; Nakirya, Doreen; Osuret, Jimmy; Isunju, John Bosco; Ssekamatte, Tonny; Mugambe, Richard
Highlights: Cooking practices are well-suited for examining water, energy and food WEF nexus interactions. Energy is the weakest link at the nexus for Kampala's poor. A social-practices approach to the WEF nexus opens up counter-intuitive spaces for intervention in advancing the SDGs. We put forward the notion of "precarious consumption" as a frame for understanding vulnerability at the WEF nexus. Abstract: Sub-Saharan African cities like Kampala face challenges with rapid urbanization and impacts of climate change. These challenges have exacerbated the struggle to provide adequate infrastructural and socio-ecological services to Kampala's growing poor. Based on a social practices perspective, this paper presents a study of emergent vulnerabilities at the urban Nexus of water, energy and food (WEF) in the informal settlements of Bwaise and Kanyogoga. We employ methods of observation, interviews, focus group discussions and a vision-building workshop to explore the growing vulnerabilities of poor households as they daily navigate deteriorating water quality, rising energy prices and food insecurity. Results indicate that most household-level vulnerabilities relate to energy poverty. Households scale back on water treatment practices such as boiling and the cooking of highly-nutritious yet energy-demanding foods such as beans in efforts to conserve charcoal. Emergent practices of everyday resilience-building include the use of biomass briquettes as an alternative to solid charcoal as well as social networks and capital which allow households to borrow food and energy. We suggest the notion of 'precarious consumption' as a tool for understanding emergent everyday vulnerabilities in relation to the urban WEF Nexus service provision and resilience policy-making in cities of the Global South.